Ankylosing spondylitis, aortic regurgitation, acetabular dysplasia and osteoarthritis of the hip : an epidemiological survey in a Norwegian Sámi population - Johnsen, Knut (Universitetet i Tromsø, 2009)
The papers of the thesis are not available in Munin: 1. Knut Johnsen, Jan Tore Gran , Knut Dale and Gunnar Husby: «The prevalence of ankylosing spondylitis among Norwegian Samis (Lapps)», J Rheumatol 1992; 19(10):1591-1594. Check availability 2. Knut Johnsen, Markku Mähönen and Per Lunde: «Prevalence estimation and follow-up of aortic regurgitation subjects in a Norwegian Sámi population», Scandinavian Cardiovascular Journal, 2009; Vol. 43, No. 3, Pages 176-180 (Informa Healthcare). Available at http://dx.doi.org/10.1080/14017430802535055 3. Knut Johnsen, Rasmus Goll and Olav Reikerås: «Acetabular dysplasia in Sámi population: a population study among Sámi in north Norway», International Journal of Circumpolar Health 67:1 2008 (International Association of Circumpolar Health Publishers). Available at http://ijch.fi/issues/671/Johnsen.pdf 4. Knut Johnsen, Rasmus Goll and Olav Reikerås: «Acetabular dysplasia as an aetiological factor in development of hip osteoarthritis», International Orthopaedics, Volume 33, Number 3 (Springer). Available at http://dx.doi.org/10.1007/s00264-008-0554-7